2019
DOI: 10.1080/1331677x.2019.1650652
|View full text |Cite
|
Sign up to set email alerts
|

Investor sentiment, momentum, and stock returns: an examination for direct and indirect effects

Abstract: This paper aims to analyse the impact of behavioural biases on asset pricing by hypothesising that sentiment and momentum are relevant risk factors in Pakistan equity market. The paper also examines the influence of sentiment and momentum factors on market risk, size, and value premiums by estimating the interacted asset-pricing model. To carry out the empirical analysis, monthly stock returns of firms listed on Pakistan Stock Exchange are used for the period 2000-2013. The empirical results indicate that both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…Ahmed et al (2019) measure the herding behavior in Pakistani financial market through secondary data and found the significant herding behavior. In this connection, Rashid et al (2019) reported that investors’ sentiment and momentum factors significantly impact the market risk, size, and value premiums in the prediction of stock returns.…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Ahmed et al (2019) measure the herding behavior in Pakistani financial market through secondary data and found the significant herding behavior. In this connection, Rashid et al (2019) reported that investors’ sentiment and momentum factors significantly impact the market risk, size, and value premiums in the prediction of stock returns.…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Han and Li [26] reveal that investor sentiment can predict China's stock market returns in the short term, different from the United States and other developed financial markets; and China's investor sentiment is a reliable momentum indicator for predicting monthly market returns; therefore, they propose a profitable trading strategy based on China's investor sentiment. Rashid et al [27] find investor sentiment has a significant impact on the required rate of returns. Baker et al [17]; Hribar and Mcinnis [28]; Stambaugh et al [11]; Neely et al [29]; and Baek [30] obtain similar conclusions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The theory assumed that no investor has insider information concerning the market and this may not apply. In addition, other factors that make it difficult for the efficient market hypothesis to hold, such as market fluctuation and economic instability and forecasting about stock prices (Rashid, Fayyaz & Karim 2019;Dalika & Seetharam 2015;Alajekwu, Obialor & Okoro (2017).…”
Section: Theoretical Review: Efficient Market Hypothesismentioning
confidence: 99%
“…In Pakistan, Rashid, Fayyaz and Karim (2019) examined the influence of investor sentiment on stock market returns. The secondary data was obtained from listed firms on the Pakistan Stock Exchange for thirteen years (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013).…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation